Common Variants at 10 Genomic Loci Influence Hemoglobin A1C Levels via Glycemic and Nonglycemic Pathways - Soranzo, Nicole; Sanna, Serena; Wheeler, Eleanor; Gieger, Christian; Radke, Dörte; Dupuis, Josée; Bouatia-Naji, Nabila; Langenberg, Claudia; Prokopenko, Inga; Stolerman, Elliot; Sandhu, Manjinder S.; Heeney, Matthew M.; et al. (Diabetes (New York, N.Y.), 2010)
OBJECTIVE: Glycated hemoglobin (HbA1c), used to monitor and diagnose diabetes, is influenced by average glycemia over a 2- to 3-month period. Genetic factors affecting expression, turnover, and abnormal glycation of hemoglobin could also be associated with increased levels of HbA1c. We aimed to identify such genetic factors and investigate the extent to which they influence diabetes classification based on HbA1c levels. RESEARCH DESIGN AND METHODS: We studied associations with HbA1c in up to 46,368 nondiabetic adults of European descent from 23 genome-wide association studies (GWAS) and 8 cohorts with de novo genotyped single nucleotide polymorphisms (SNPs). We combined studies using inverse-variance meta-analysis and tested mediation by glycemia using conditional analyses. We estimated the global effect of HbA1c loci using a multilocus risk score, and used net reclassification to estimate genetic effects on diabetes screening. RESULTS: Ten loci reached genome-wide significant association with HbA1c, including six new loci near FN3K (lead SNP/P value, rs1046896/P = 1.6 x 10-26), HFE (rs1800562/P = 2.6 x 10-20), TMPRSS6 (rs855791/P = 2.7 x 10-14), ANK1 (rs4737009/P = 6.1 x 10-12), SPTA1 (rs2779116/P = 2.8 x 10-9) and ATP11A/TUBGCP3 (rs7998202/P = 5.2 x 10-9), and four known HbA1c loci: HK1 (rs16926246/P = 3.1 x 10-54), MTNR1B (rs1387153/P = 4.0 x 10-11), GCK (rs1799884/P = 1.5 x 10-20) and G6PC2/ABCB11 (rs552976/P = 8.2 x 10-18). We show that associations with HbA1c are partly a function of hyperglycemia associated with 3 of the 10 loci (GCK, G6PC2 and MTNR1B). The seven nonglycemic loci accounted for a 0.19 (% HbA1c) difference between the extreme 10% tails of the risk score, and would reclassify similar to 2% of a general white population screened for diabetes with HbA1c. CONCLUSIONS: GWAS identified 10 genetic loci reproducibly associated with HbA1c. Six are novel and seven map to loci where rarer variants cause hereditary anemias and iron storage disorders. Common variants at these loci likely influence HbA1c levels via erythrocyte biology, and confer a small but detectable reclassification of diabetes diagnosis by HbA1c.